PERBEDAAN TINGKAT KONSUMSI DAN KADAR KOLESTEROL DARAH ANTARA PEROKOK DAN NON PEROKOK - Dina Fahmawati (The Indonesian Journal of Public Health, 2019)
Cigarette smoke contains nicotine which disturbs health. Nicotine is capable of reducing the taste of food, so  there is appetite suppressant. The ability of nicotine in increasing blood liposuction process can affect the increase in blood cholesterol level. The research aims to study the difference between food intake and blood cholesterol level between smokers and non-smokers. This study was a comparative observational analytic study using cross-sectional design. The data of particular  subjects and smoking habit were  obtained from the questionnaire. The food intake was obtained by interview using 2x24 hours food recall form while the blood cholesterol level was obtained by blood sampling which was then analyzed using laboratory test. The subjects were 13 smokers and 13 non-smokers, taken by simple random sampling. The data were analyzed by Independent t-Test. The results have suggested that the difference in the average  food intake and  blood cholesterol level between smokers and non-smokers were not significant. The substantial average difference was found in the level of cholesterol intake, so  the statistical test has showed a significant difference, p-value = 0.005 < α(0.05). Smoking has a harmful effect for health so  people must decrease its consumption or stay abstinent from it. The longer human get exposed to cigarette, the more susceptible they get the illness from it.